2018
DOI: 10.1021/acs.inorgchem.8b00559
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Control of Supramolecular Chloride Photorelease

Abstract: Supramolecular assembly is shown to provide control over excited-state chloride release. Two dicationic chromophores were designed with a ligand that recognizes halide ions in CHCl and a luminescent excited state whose dipole was directed toward, 1, or away, 2, from an associated chloride ion. The dipole orientation had little influence on the ground-state equilibrium constant, K ∼ 4 × 10 M, but induced a profound change in the excited-state equilibrium. Light excitation of [1,Cl] resulted in time-dependent sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 62 publications
2
19
0
Order By: Relevance
“…Coulombic repulsion will move the iodide in the tmam pocket away from the 3,3′-H atoms of the bipyridine toward the cationic amines. Indeed, prior research has shown full photorelease of chloride anions associated with a ligand where the excited state resides . Coulombic repulsion of the other iodide is expected to be less, as it is not directly associated with the tmam ligand, and may be attracted to the more Lewis acidic Ru III .…”
mentioning
confidence: 99%
“…Coulombic repulsion will move the iodide in the tmam pocket away from the 3,3′-H atoms of the bipyridine toward the cationic amines. Indeed, prior research has shown full photorelease of chloride anions associated with a ligand where the excited state resides . Coulombic repulsion of the other iodide is expected to be less, as it is not directly associated with the tmam ligand, and may be attracted to the more Lewis acidic Ru III .…”
mentioning
confidence: 99%
“…The electronic coupling between the ions is expected to be smaller for the solvent-separated ion pairs than for the contact ion pair. Common techniques to investigate the nature of ion pairs, which are encompassed in the broader context of host–guest chemistry, are NMR, ,,, UV–visible, ,,,,,,, and photoluminescence spectroscopy ,,,,,,, as well as isothermal titration calorimetry (ITC). , To quantify ion pair structures without excited-state reactivity, Ward et al utilized chloride as an “innocent” ion, as its large reduction potential precluded excited-state electron transfer . A series of ruthenium complexes, i.e., [Ru­(bpy) 3–x (deeb) x ] 2+ where x = 0, 1, 2 or 3, and chloride was studied by 1 H NMR, UV–vis, and photoluminescence spectroscopy in CH 2 Cl 2 .…”
Section: Halide Photoredox Chemistry With Metal-to-ligand Charge-tran...mentioning
confidence: 99%
“…The colored arrow indicates the time dependent spectral shift measured. Reproduced with permission from ref . Copyright 2018 American Chemical Society.…”
Section: Halide Photoredox Chemistry With Metal-to-ligand Charge-tran...mentioning
confidence: 99%
See 1 more Smart Citation
“…Follow up work by the same group further studied the halide photorelease concept using RU23 to RU27 with chloride and bromide. 67,68 Fig. 10.…”
Section: Indirectmentioning
confidence: 99%